Giant Paratubal Cyst Mimicking Mesenteric Cyst - Ebrahim Almahmeed; Abdulaziz Alshaibani; Hamad Alhamad; Abdulmenem Abualsel (Case Reports in Surgery)
Paratubal cysts are adnexal masses located in the broad ligament; whenever the size of the cyst is >20 cm, it is considered a giant cyst and can present with complications including ovarian torsion and perforation. Diagnosis can be made clinically with the help of radiological investigations, although the gold standard diagnostic tool is diagnostic laparoscopy. Managing this condition relies mainly on surgical intervention (open or laparoscopic). Giant paratubal cysts carry challenges in their surgical excision as they carry a higher risk of spillage. We present a case of giant paratubal cyst in a 26-year-old Bahraini female who presented with abdominal distension and pain for 3 years.